Characterization of Odor‐Active Compounds in Gabiroba Fruits (Campomanesia xanthocarpa O. Berg). Issue 2 (29th October 2015) - Ferreira, Daniele De Freitas; Garruti, Deborah Dos Santos; Barin, Juliano Smanioto; Cichoski, Alexandre José; Wagner, Roger
Abstract: Headspace solid‐phase microextraction was used for isolation of the volatile compounds from gabiroba fruit ( C ampomanesia xanthocarpa  O. Berg) and further quantification by gas chromatography–flame ionization detector and identification by gas chromatography/mass spectrometry and gas chromatography–olfactometry (GC‐O). The odor‐active compounds were evaluated using the Osme technique. Seventy‐nine compounds were identified, from which 39 presented odor activity detected by the judges in GC‐O analysis. The major compounds were ( E )‐2‐hexenal, ethanol, ethyl hexanoate, hexanal, ethyl butanoate, hexanoic acid, 1‐hexanol, ( E )‐2‐hexen‐1‐ol, linalool, 1‐butanol, methyl acetate and α‐terpineol, but the substances 4‐hydroxy‐2, 5‐dimethyl‐2(3 H )‐furanone, 1‐penten‐3‐ol, an unidentified compound, hexanal, ( E, E )‐2, 4‐hexadienal, ( Z )‐3‐hexen‐1‐ol, ethyl hexanoate, γ‐eudesmol, linalool and β‐eudesmol were related to the aroma of this fruit. The green and sweet notes were perceived in high frequency of description and intensity, and they were considered important for the characteristic gabiroba aroma. Practical Applications: Gabiroba is a native fruit from South America with an intense and pleasant flavor, but there is a few information regarding to its chemical profile of volatile compounds. In this work, the compounds that better represent the gabiroba aroma (odor‐active substances) were determined by olfactometric analysis. This information was crucial for sensory characterization of fruit and could be used as a tool for evaluation of processing and postharvest quality.